SLOPE STABILITY ANALYSIS DUE TO INFRASTRUCTURE DEVELOPMENT OF RATU BOKO SITE YOGYAKARTA UNDER EARTHQUAKES LOADING - Rifa'i, Ahmad; Putra, Okri Asfino (Journal of Applied Engineering Science, 2021)
The Ratu Boko site is a cultural heritage that has a high historical value and located about 30 kilometers to the east of Yogyakarta. Instability of the slope occurred due to the Yogyakarta earthquake in 2006, and it was indicated by the occurrence of cracks in the resto building that built on the top of the hill. The first reinforcement of the columns and foundations of the outside building was used a reinforced concrete that built-in 2012. The similar reinforcement on the inside building column and foundation was finished in 2017. In this research the displacement of the reinforced foundation, and slope stability generally both in safety factor and deformation were evaluated. The deformation and displacement analysis of the foundation were solved using Finite Element Analysis. On the other hand, for the safety factor of the slope, Limit Equilibrium Method was used. The simulation is divided into several stages, starting from the existing condition, after the first and second reinforcement, and also after increasing load due to development plan. Based on the numerical simulation, the horizontal displacement on the foundation of Plaza Andrawina decreases after the first and second reinforcement was installed. The horizontal displacement is significantly decreased in both foundations for 9.44 mm and 8.03 mm. Furthermore, the safety factor of the slope increases after the first and second reinforcement was installed. The slope safety factor using a maximum acceleration of 0.30g is 1.318. These obtained results are relatively safe from slope failures
Keywords: Yogyakarta, Indonesia, reinforcement, slope stability, safety factor